2018
DOI: 10.1155/2018/5903451
|View full text |Cite
|
Sign up to set email alerts
|

The Spatiotemporal Variations of Runoff in the Yangtze River Basin under Climate Change

Abstract: A better understanding of the runoff variations contributes to a better utilization of water resources and water conservancy planning. In this paper, we analyzed the runoff changes in the Yangtze River Basin (YRB) including the spatiotemporal characteristics of intra-annual variation, the trend, the mutation point, and the period of annual runoff using various statistical methods. We also investigated how changes in the precipitation and temperature could impact on runoff. We found that the intra-annual runoff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Several previous studies have estimated the hydrological change response to climate change over the YRB. Xiao et al [10] analyzed the intra-annual variations, tendencies, and mutational sites of runoff during the historical period in the YRB. Gu et al [11] found that the runoff in the northern part of the Yangtze River will increase by approximately 10% from 2070 to 2099 due to climate change according to RegCM4.0 of the SRES A1B scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have estimated the hydrological change response to climate change over the YRB. Xiao et al [10] analyzed the intra-annual variations, tendencies, and mutational sites of runoff during the historical period in the YRB. Gu et al [11] found that the runoff in the northern part of the Yangtze River will increase by approximately 10% from 2070 to 2099 due to climate change according to RegCM4.0 of the SRES A1B scenario.…”
Section: Introductionmentioning
confidence: 99%
“…These statistical methods include the Cumulative Anomaly Curve Method [25], Mann-Kendall (MK) Nonparametric test [26], Linear/Nonlinear regression analysis, T test, and etc. [27,28]. Besides these technologies, wavelet analysis has received increasing attention and has been widely applied to many fields of hydrology to elucidate localized characteristic of non-stationary time series both in temporal and frequency domains.…”
Section: Introductionmentioning
confidence: 99%
“…It can be used to describe the average variation of interdecadal variability quantitatively. For sequence x, the cumulative anomaly of t at a certain time is expressed as [29]:…”
Section: Cumulative Anomaly Methodsmentioning
confidence: 99%
“…Meng et al [28] used linear regression, five-year moving average, the Mann-Kendall test, cumulative variance analysis, and Pettitt to test changes in temperature and precipitation in the Hexi Corridor, Northwest China's Gansu province. Using various statistical methods, temporal and spatial characteristics, trends, and abrupt points, the annual variation periods of temperature and precipitation in the Yangtze River basin of China have been analyzed [29]. In addition, based on available data, researchers can analyze future trends of temperature and precipitation.…”
Section: Introductionmentioning
confidence: 99%